Moderating Effect of Application of Accounting Technology on Audit Quality - Amos O. Akinola; Peter S. Daramola; Timilehin E. Adenle (Cihan University-Erbil Journal of Humanities and Social Sciences, 2025)
This study examines the moderating effect of accounting technology (AT) on audit quality. Primary data were sourced from hundred and fourteen auditors in private practice using a questionnaire drawn on a four-point Likert scale. Both the internal reliability and validity of the instrument were established. Three hundred and eighty-nine participants filled and returned, while three hundred and sixty two were found valid for the study and subjected to analysis using a regression model to test hypotheses one and two while the third hypothesis was subjected to LSM-SEM. The results of the analysis show that there is a positive significant (R2 = 0.554, Pvalue = 0.000) moderating effect of AT on the technical quality of audits and on the service quality of audits (R2 = 0.840, p-value = 0.000). The joint moderating effect of AT was found to have a substantial, positive, and significant effect (adjusted R2 of 0.849, Pvalue = 0.000) on audit quality, while Q2 of 0.540 established the fact that there is a large degree of relevance of the structural model employed for the joint effect. It is therefore recommended that standard-setting boards provide the necessary guidelines to drive audit quality in this era of accounting technology. Additionally, there is a need to conduct studies with a wider scope across regions.